Necrolytic Acral Erythema: Current Insights - Inamadar AC; Shivanna R; Ankad BS (Dove Medical Press, 2020)
Arun C Inamadar,1 Ragunatha Shivanna,2 Balachandra S Ankad3 1Department of Dermatology, Venereology and Leprosy, Sri BM Patil Medical College, BLDE University, Vijayapura 586103, Karnataka, India; 2Department of Dermatology, Venereology and Leprosy, ESIC Medical College and PGIMSR, Bengaluru 560010, Karnataka, India; 3Department of Dermatology, Venereology and Leprosy, SN Medical College, Bagalkote 587102, Karnataka, IndiaCorrespondence: Arun C InamadarDepartment of Dermatology, Venereology and Leprosy, Sri B.M. Patil Medical College, BLDE University, Vijayapura, Karnataka, IndiaTel +91 94 4810 2920Email aruninamadar@gmail.comAbstract: Necrolytic acral erythema (NAE) is now considered as a distinct clinical entity. It clinically presents as well demarcated hyperpigmented papules and plaques with thick adherent scales distributed symmetrically over dorsum of feet. It usually develops in patients with Hepatitis C virus (HCV) infection. Cases of NAE have been reported in patients without HCV infection. Hepatic dysfunction resulting in metabolic alterations like hypoalbuminemia, hypoaminoacidemia, hyperglucagonemia and transient zinc deficiency has been proposed as underlying pathogenic mechanism of NAE. Clinically, NAE resembles other necrolytic erythemas like necrolytic migratory erythema (NME), acrodermatitis enteropathica (AE) and pellagra. Better understanding of etiopathogenesis and histopathological features is important to distinguish NAE from other necrolytic erythemas. The disease runs a natural course of exacerbations and remissions. Non-invasive diagnostic tools like dermoscopy can be used in differential diagnosis of NAE. Oral zinc therapy is the most effective treatment of NAE reported in most of the cases irrespective of HCV status or serum zinc levels.Keywords: NAE, necrolytic acral erythema, zinc, glucagonoma, hepatitis